Bayesian optimisation with transfer learning for NASICON-type solid electrolytes for all-solid-state Li-metal batteries. Issue 47 (26th October 2022) - Fukuda, Hiroko; Kusakawa, Shunya; Nakano, Koki; Tanibata, Naoto; Takeda, Hayami; Nakayama, Masanobu; Karasuyama, Masayuki; Takeuchi, Ichiro; Natori, Takaaki; Ono, Yasuharu
Abstract : Demonstrate BO approaches to search for optimal composition with high ionic conductivity efficiently. Abstract : NASICON-type LiZr2 (PO4 )3 (LZP) has attracted significant attention as a solid oxide electrolyte for all-solid-state Li-ion or Li-metal batteries owing to its high Li-ion conductivity, usability in all-solid-state batteries, and electrochemical stability against Li metal. In this study, we aim to improve the Li-ion conductivity of Li-rich NASICON-type LZPs doped with CaO and SiO2, i.e., Li1+ x +2 y Ca y Zr2− y Si x P3− x O12 (0 ≤ x ≤ 0.3, 0 ≤ y ≤ 0.3) (LCZSP). Herein, a total of 49 compositions were synthesised, and their crystal structures, relative densities, and Li-ion conductivities were characterised experimentally. We confirmed the improvement in Li-ion conductivity by simultaneous replacement of Zr and P sites with Ca and Si ions, respectively. However, the intuition-derived determination of the composition exhibiting the highest Li-ion conductivity is technically difficult because the compositional dependence of the relative density and the crystalline phase of the sample is very complex. Bayesian optimisation (BO) was performed to efficiently discover the optimal composition that exhibited the highest Li-ion conductivity among the samples evaluated experimentally. We also optimised the composition of the LCZSP using multi-task Gaussian process regression after transferring prior knowledge of 47 compositions of Li1+ x +2 y Y x Ca y Zr2− x − y P3 O12 (0 ≤ x ≤ 0.376, 0 ≤ y ≤ 0.376) (LYCZP), i.e., BO with transfer learning. The present study successfully demonstrated that BO with transfer learning can search for optimal compositions two times as rapid as the conventional BO approach. This approach can be widely applicable for the optimisation of various functional materials as well as ionic conductors.